Southern African Customs Union agreement 2002 (as amended on 12 April 2013 between the Governments of the Republic of Botswana, the Kingdom of Lesotho, the Republic of Namibia, the Republic of South Africa and the Kindgom of Swaziland (Southern African Customs Union Secretariat WindhoekNA, 2013)
Presents the text of the agreement.
Keywords: INTERNATIONAL AGREEMENTS